CHARACTERIZING LOAD LIMIT OFFENCES IN INDONESIA: A STATISTICAL APPROACH ON OVERLOADING CASES AT WBSS - IGW. Samsi Gunarta; Idwan Santoso; Bambang Ismanto; Pradono Pradono (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Overloading has caused headache to Indonesian Road Authority due to its rates and severity. The Directorate General of Land Communication (DGLC) suspected mismanagement of Weigh Bridge Station (WBS) significantly contributes to the in effectiveness of WBS in deterring overloading offences from the road network. A change was set up by involving private sector in WBS management. Four WBSs in Sumatra were included in the pilot project. This paper utilized the data provided by the pilot project to characterize overloading offences captured by the WBSs.Three hundred sixty (360) cases were randomly selected from over 10,000 cases of 4 WBSs. Descriptive and crosstabs analyses were conducted indicating that overloading has not been simply related to trucking cost coverage but rather related to the utilization of resources in freight transport. Deeper understanding by conducting insight look towards the motivation of overloading is strongly recommended in solving the problem of overloading. Keywords : Overloading Offences, Weigh Control, Freight Transport, overload countermeasure